Spatial topographic roughness (RMSh) for all along-flow flightlines of the bed topography of the Northeast Greenland Ice Stream, downstream of the EastGRIP ice core site (2018 and 2022 NEGIS surveys) - Charlotte Carter; Steven Franke; Daniela Jansen; Olaf Eisen (PANGAEA, 2025)
The Northeast Greenland Ice Stream (NEGIS) is an elongated feature extending ~600 km into the interior of the Greenland Ice Sheet. Here, we investigate detailed subglacial topography along the length of the NEGIS to ascertain the characteristics of the ice stream bed. Spatial topographic roughness describes the standard deviation of vertical change in bed elevation over a given horizontal distance (Root Mean Square height, or RMSh). RMSh values were derived from ice thickness data from AWI extquotesingles P5-233_NEGIS_2022 and P6-211_EGRIP_NOR_2018 flight campaigns, where the majority of profiles were oriented parallel or perpendicular to ice flow direction. A moving window size of 960 m (64 data points) was used to calculate RMSh, and values are omitted where gaps in the ice thickness data were present. Roughness anisotropy was also calculated at the intersection of two flightlines, as the ratio between along- and across-flow roughness.
In: Carter, C et al. (2025): Spatial topographic roughness of the bed topography of the Northeast Greenland Ice Stream, downstream of the EastGRIP ice core site [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.984362